Forms of translanguaging in Zimbabwe’s classrooms: are the practices useful or useless in the teaching and learning of STEM subjects? - Svongoro, Paul; Kondowe, Wellman (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
Although translanguaging is a growing discipline in the field of education in other parts of the world, it is still under-researched in Zimbabwe. However, Zimbabwean teachers often use various forms of translanguaging to engage their students and help them use their full linguistic resources in academic subjects. This study aimed to explore the various forms of translanguaging used by STEM subject teachers in Mutare, Zimbabwe, assess their effectiveness, and propose the most useful form(s) based on the learners' level and the language demographics of their classes. Data for the study were collected through observation of STEM classes at selected schools and tertiary institutions in Mutare, Zimbabwe, and three Focus Group Discussions with 29 STEM subject teachers and lecturers from 11 institutions from Mutare Urban District. The collected data were analyzed using Makalela’s (2016) Ubuntu Translanguaging Pedagogy (UTP). The study found that most STEM subject teachers have embraced translanguaging as a normal practice in multilingual classrooms. Furthermore, the study established that instructors at different levels are beginning to appreciate that translanguaging is a strategy they can use to help students draw on all their linguistic resources when reading, writing, and discussing academic subjects in a new language. STEM teachers adopted different forms of translanguaging for different learners. The conclusion the study makes is that, when STEM subject teachers use translanguaging, a student's home language can serve as a scaffold for learning additional languages and academic content in the new language, leading to better engagement and involvement of learners in subjects often perceived as difficult
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 8, 2024
Keywords: Bilingual classrooms; STEM subjects; Translanguaging; Education, bilingual; Education, urban -- Zimbabwe; Linguistics; Translanguaging (Linguistics)